2014
DOI: 10.1039/c4ay00767k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of five quaternary ammonium compounds in foodstuffs using high performance liquid chromatography-tandem mass spectrometry

Abstract: A HPLC-MS/MS was devcloped and applied for the determination of quaternary ammonium compounds in food samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Overall, it was concluded that these fragmentation results confirm DDAC being among the compound(s) responsible for the antimicrobial activity in sample III. These results also match with previously reported findings (Cao et al 2014). The properties of DDAC comply with the observed shift in RT in the fractionation systems.…”
Section: Sample III (Unknown)supporting
confidence: 82%
See 1 more Smart Citation
“…Overall, it was concluded that these fragmentation results confirm DDAC being among the compound(s) responsible for the antimicrobial activity in sample III. These results also match with previously reported findings (Cao et al 2014). The properties of DDAC comply with the observed shift in RT in the fractionation systems.…”
Section: Sample III (Unknown)supporting
confidence: 82%
“…Figure 3(a). The molecular ion at m/z 326.378 is clearly observed and also two previously reported product ions were observed: m/z 186.2216 and m/z 57.0702 (Cao et al 2014). …”
Section: Sample III (Unknown)mentioning
confidence: 55%
“…The concentration of QACs, and surfactants in general, can be reliably measured using liquid chromatography-tandem mass spectrometry (LC-MS/MS), for example, BAC, alkyltrimethylammonium chloride, DDAC, and Triton X-100 in various environmental and food samples. [5][6][7][8][9][10][11] For instance, Brownawell et al and Jiang et al identified and quantified BAC and diallyldimethylammonium chloride in the concentration range of micrograms per gram, from sediments and sewage sludges, using reversed-phase liquid chromatography-mass spectrometry (LC-MS). 5,6 Residual QACs in food samples such as vegetables, meat, and dairy products were also determined via LC-MS by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Residual QACs in food samples such as vegetables, meat, and dairy products were also determined via LC-MS by different groups. [7][8][9] In these methods, the QAC concentrations were measured in the range of 5-500 μg/kg, in which the upper range of the concentrations is above the CMCs of long-chain QACs, for example, C16 and C18. For the Triton X-100 surfactant, which is a nonionic surfactant that has a polyethylene oxide chain, the Horváth group recently developed an analytical method based on hydrophilic interaction LC and estimated its elution time profile by applying a quadratic retention model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation